MENINGKATKAN KETERAMPILAN SOSIAL ANAK MELALUI PERMAINAN TRADISIONAL DI DUSUN CITEUREUP II - Hani Khulsum; Ikhwan Rahmanto; Setyo Supratno (An-Nizam, 2022)
This study aims to provide data and information about efforts to improve children's social skills through traditional game playing methods in Citeureup II Hamlet, Kutamukti, Karawang. The research method used is the community education method, which consists of sharing section activities as an initial action, then actions in the form of playing traditional games with children and ending with a sharing section again as a form of reflection to find out the development of social skills in children. Data collection techniques use questionnaires (pre-test and post-test), interviews and observations. The sample in this study consisted of 20 children aged 10-12 years. The results of the pre-test showed that the total score obtained was 1049. After the implementation of the community education method through traditional games which was carried out for 5 days, it resulted in a pos-test result score of 1482 or there was an increase in the score of 447 from the total score of the previous pretest. shows that traditional games are effective in improving children's social skills.